Revisiting Polygamous Marriage Laws in Malaysia: Addressing Enforcement Gaps and Contemporary Challenges in Islamic Family Law - Zuliza Mohd Kusrin; Aishah Mohd Nor; Shadli Sabarudin; Ruzita Ramli (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
This article examines the legal framework governing polygamous marriages in Malaysia, focusing on Section 23 of the Islamic Family Law (Federal Territories) Act 1984, which requires men to obtain prior Sharia Court consent before contracting additional marriages. Despite this requirement, the prevalence of polygamous marriages solemnised without court approval underscores significant enforcement weaknesses. Legal loopholes allow such marriages to be legitimised and registered post-facto, provided they comply with Hukum Syarak and the associated matrimonial offence is resolved through prescribed penalties. Employing doctrinal legal analysis alongside an examination of unreported Sharia Court files, the findings reveal inconsistencies in judicial discretion when sentencing offenders, highlighting gaps that undermine the regulatory objectives of polygamy laws and erode public confidence in the Sharia legal system. Within the maqāṣid al-sharīʿah framework, the research demonstrates that circumventing procedural safeguards compromises the objectives of Islamic law, particularly the protection of lineage (ḥifẓ al-nasl), the welfare of spouses and children, and overall family harmony. Women and children in unregulated marriages face legal insecurity, inequitable treatment, and restricted access to maintenance and inheritance rights. The study concludes that comprehensive reforms are necessary to strengthen enforcement, close regulatory gaps, and harmonise administrative compliance with religious validity. This study contributes to the academic discourse by offering recommendations that include enhancing penalties, standardising judicial discretion, raising public awareness and education about the legal implications of unregistered polygamous marriages to women and children, and integrating maqāṣid principles to prioritise justice, equity, and family welfare. By addressing both legal and ethical dimensions, these reforms aim to safeguard the rights of all parties in polygamous marriages and enhance public confidence in Malaysia's Sharia legal system